Volatility of international commodity prices in times of Covid-19: Effects of oil supply and global demand shocks - Hillary Chijindu Ezeaku; Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2020)
This study examines the effects of oil supply and global demand shocks on the volatility of commodity prices in the metal and agricultural commodity markets using the SVAR model. The empirical evidence is based on real time daily closing international commodity prices covering the period 2 December 2019 to 1 October 2020. The findings are presented in cumulative impulse responses and variance decompositions. The former is utilized to examine the accumulated influence of structural shocks on the volatility of agricultural and metal commodities whereas the latter reflect the share of variation in the volatility of each commodity arising from each structural shock. Various patterns are provided on how metal and agricultural commodity prices have been influenced by the COVID-19 pandemic. Policy implications are discussed.
Keywords: H12; I12; O10; 330; Covid-9; Commodity Prices